Aberrant claw forms in the Annulipes Group of mosquitoes (Diptera: Culicidae: Aedes) in Germany - Kuhlisch, Cornelius; Kampen, Helge; Werner, Doreen (Zootaxa, 2020)
Specimens of five species of the culicid Annulipes Group (Aedes annulipes, Ae. cantans, Ae. excrucians, Ae. flavescens, Ae. riparius), collected in the framework of the German mosquito monitoring programme, were examined for aberrant tarsal claws. Twenty types of aberrations regarding position, size, multiplication and structural modification of the tarsal claw and its basal tooth that were detected are described and illustrated. Different basal tooth positions found on claws reveal a basic blueprint of possible positions on mosquito tarsal claws. Morphological peculiarities and asymmetric occurrence of the aberrant claw types, as well as possible causes, are discussed with respect to species and gender.